Perbedaan Stres Kerja dalam Pelaksanaan Work from Office Pasca Pandemi Covid-19 ditinjau dari Tipe Kepribadian dada Pegawai Administrasi Universitas Medan Area - Simbolon, Arissa; Meliala, Shirley Melita Sembiring (Universitas Medan Area, 2024)
This research aims to determine the differences in work stress in implementing work from the office after the Covid-19 pandemic in terms of personality types in administrative employees at Medan Area University. This comparative quantitative research involved 38 Medan Area University administrative employees taken using total sampling. Work stress data was collected using a Likert scale, personality type using the Guttman scale, and analyzed using the independent t-test. The results of the analysis show that there is a significant difference in the level of work stress between employees with type A and type B personalities, with a significance value of 0.002 0.05. Based on calculations, Medan Area University administrative employees who have type A personalities show work stress in the moderate category, which can be seen from the average value (mean) of 100.73 with a standard deviation of 17.18. Meanwhile, employees with type B personality have work stress in the low category, with an average score of 86.19 and a standard deviation of 8.82. These findings support the hypothesis that employees with type A personalities tend to experience higher levels of work stress compared to employees with type B personalities.